Pengaruh Likuiditas, Aktivitas Dan Pertumbuhan Penjualan Terhadap Profitabilitas Pada Perusahaan Subsektor Telekomunikasi Di Bursa Efek Indonesia - Tulung Allo, Grasela; Sofyaun, Ashari; Matyani, Matyani (Jurnal GeoEkonomi, 2025)
The Influence of Liquidity, Activity, and Sales Growth on Profitability in the Telecommunications Subsector Companies Listed on the Indonesia Stock Exchange." The objective of this research is to determine the influence of Liquidity (Current Ratio), Activity (Total Asset Turnover), and Sales Growth on Profitability in Telecommunications Subsector Companies listed on the Indonesia Stock Exchange. In this study, the population consists of 18 companies, and a sample of 11 companies was selected based on specific criteria set by the author. The method used in this research is multiple regression analysis with secondary data obtained from the companies' financial statements for the period of 2020 to 2023. The results indicate that liquidity has a significant effect on profitability, activity does not have a significant effect on profitability, and sales growth does not have a significant effect on profitability